2005
DOI: 10.2172/850553
|View full text |Cite
|
Sign up to set email alerts
|

Source Phenomenology Experiments in Arizona

Abstract: The Source Phenomenology Experiments (SPE) were conducted at mines in northeastern and southeastern Arizona in the summer of 2003. The Arizona experiments have resulted in an important dataset for the nuclear monitoring community by providing data to address a number of source parameter issues. We designed, detonated, and recorded ten single-fired explosions at a copper mine in southeast Arizona and nine single-fired explosions in a northern Arizona coal mine. The single-fired explosions ranged in size from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The dedicated shots have a similar behavior and have been shown to approximately match Mueller and Murphy (1971) explosion spectra (e.g. Bonner et al, 2005). In contrast, the production shots have much stepper falloff with frequency.…”
Section: Coda Derived Source Spectramentioning
confidence: 65%
See 2 more Smart Citations
“…The dedicated shots have a similar behavior and have been shown to approximately match Mueller and Murphy (1971) explosion spectra (e.g. Bonner et al, 2005). In contrast, the production shots have much stepper falloff with frequency.…”
Section: Coda Derived Source Spectramentioning
confidence: 65%
“…A list of the shots sizes, depths, yields and scaled yields are given in Table 1 and 2. More detail about the geology of each mine and the layout and execution of the dedicated shots can be found in the earlier chapters of this report and in Bonner et al (2005). (Bonner et al, 2005).…”
Section: The Spe Experiments Shotsmentioning
confidence: 99%
See 1 more Smart Citation
“…The so-called Arizona source phenomenology experiment (Bonner et al, 2005) showed that the designed test shots and mining explosions are good surrogates for nuclear explosions as the magnitude-and distance-corrected Pg/Lg amplitude ratios fall in the range of those for nuclear explosions at NTS. Differences in depth of burial and single versus multiple shots have only a small effect on the amplitude ratios.…”
mentioning
confidence: 99%